POLA KEPEMIMPINAN KEPALA SEKOLAH DALAM PENGUATAN KARAKTER DI SEKOLAH DASAR KOTA SINTANG-KALIMANTAN BARAT - Lusila Parida; Sirilus Sirhi; Daniel Dike (Profesi Pendidikan Dasar, 2019)
This study aims to describe the image of principal's leadership patterns in the formation of character values in elementary schools. The research design used a case study research at the Elementary School 07 Sintang, the Islamic Elementary School Sintang, and Elementary School Suluh Harapan Sintang. The subjects of the research used the area sampling method because of consideration of the special characteristics of the schools with reference schools, state Islamic schools and private Catholic schools. Data collection is done through observation, in-depth interviews and document studies. The selection of research subjects using the purposive sampling method. The subjects of these researches were 33 people consisting of three principals and 30 teachers. Data validity is done through the triangulation process. The results showed that the dominant leadership patterns in the three schools tended to be dominant in the instructional leader pattern. For the process of forming the students’ character to be more optimized, the principal must do a combination of leadership patterns. Transformative leadership patterns and cultural leadership must be cultivated in strengthening character by innovating strategic programs according to the conditions and abilities of the school. The character strengthening programs that are integrated into students' subjects and extracurricular for students must accommodate the six stages of the pyramid of habituation of character values.